ANALYSIS OF FINANCIAL AND ECONOMIC PREREQUISITES FOR ENSURING ECONOMIC SECURITY OF INDUSTRIAL ENTERPRISE - LIUBOKHYNETS, LARYSA; KATKOVA, TETYANA; KRAVCHYK, YURII (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the study is to introduce the author’s methodological approach to analyze the prerequisites for economic security of industrial enterprises, the formation on this basis of conclusions for priority areas of policy to strengthen it. The urgency of the problem of development of methods of analysis, monitoring and diagnostics of economic security of industrial enterprises is revealed. It is argued that the observation of the financial and economic condition of the enterprise allows to identify the prerequisites for the economic security of the industrial enterprise. The practical significance of the study is that the indicators of financial and economic condition of the industrial enterprise are revealed; the results of the analysis of the general economic and investment activity of the industrial enterprise are given; indicators of profitability and capital turnover of an industrial enterprise are analyzed; the characteristic of indicators of solvency and structure of assets of the industrial enterprise is resulted; the capital structure is revealed and the potential of the industrial enterprise to compensate for its possible losses is assessed. The obtained results are characterized from the standpoint of prerequisites for ensuring the economic security of an industrial enterprise. The comparative characteristics of financial and economic indicators of the enterprise and average industry values are given. Problematic aspects of economic security of an industrial enterprise have been identified. The scientific novelty of the study is that the methodological approach to the analysis of economic security of an industrial enterprise has been further developed, namely the method of analyzing the financial and economic prerequisites for ensuring the economic security of an industrial enterprise has been developed. Research methods - structural-logical and semantic analysis, statistical analysis, quantitative and qualitative comparison.